Co9S8@CNFs cathode enables stable aluminum storage with 3D synergy and co-dominated mechanism - Ruiyuan Zhuang; Jianhong Yang; Jian-chun Wu (Electrochemistry Communications)
Rechargeable aluminum ion batteries (AIBs) hold promises as the next generation of electrochemical energy storage systems, characterized by low cost, high specific energy, and enhanced safety. One of the primary obstacles hindering the development of AIBs is the scarcity of suitable cathode materials. Here, a novel cobalt sulfide@carbon nanofibers (Co9S8@CNFs) composite material was synthesized through electrostatic spinning, heat treatment, and sulfurization processes. The composite material consists of Co9S8 nanoparticles uniformly anchored on interconnected CNFs to form a three-dimensional (3D) porous network structure, which is conducive to the penetration of electrolyte. Structural and morphological analysis confirmed the high crystallinity of Co9S8 and its uniform distribution on CNFs. The in-situ growth of Co9S8 nanoparticles on the surface of CNFs helps shorten the migration path of electrons and effectively solves the problem of peeling off from the CNFs substrate during charging and discharging process. As a self-supporting cathode for AIBs, the electrode exhibits good cycle life. Electrochemical evaluation demonstrated a reversible discharge capacity of ∼60 mAh g−1 at 100 mA g−1 with stable cycling performance over 400 cycles. The composite cathode exhibited small charge transfer resistance and improved ion diffusion kinetics, attributed to the conductive CNFs network and 3D porous structure. First-principles calculations further elucidate the energy storage mechanism, revealing that Al3+ preferentially replaces Co atoms in the Co9S8 lattice during cycling, with a formation energy of 0.92 eV. This work emphasizes the synergistic effect of Co9S8@CNFs integration in alleviating rapid capacity degradation and enhancing structural stability, providing a promising strategy for designing high-performance AIB cathodes.